Restauro Archeologico e Restauro Librario: due diverse applicazioni del restauro virtuale per la conservazione del patrimonio dei beni culturali - Jasink, Anna Margherita; Dionisio, Giulia; Lazzi, Giovanna; Licari, Daniele (Archeomatica, 2015)
Abstract The idea of this paper is to compare the application of the physical and virtual restoration to the two apparently remote areas of the archaeological and the librarian patrimonies. The results discussed here derive from the collaboration of two Florentine institutions, the Aegean laboratory of the University and the Biblioteca Riccardiana. The specific analyzed objects pertain to the Aegean ware collections from the Archeological Museum and to the ancient Italian manuscripts with their ligatures and watermarks kept in the Riccardiana Library. This work represents an example of extended collaborations that should be profitably implemented among different fields and institutions.